O problema da caracterização das convenções da OIT como tratados de direitos humanos e suas consequências no direito brasileiro - Galvão, Januário Cicco Wanderley (2016)
In spite of great development of the Human Rights International Law, the conceptualizations of human rights treaties are vague and unprecise. In relation to ILO’s Conventions, there are three different chains in doctrine which refer to absolute inappropriate criteria to characterize them as human rights treaties, what makes things even more difficult. This problem may have resulted in the unconstitutionality of the internalization process of the Conventions approved since the 3th paragraph was included to article 5 of the Brazilian Constitution by the Amendment number 45/2004. Since the cited amendment entered into force, none of the six Conventions already approved by Brazilian Congress have been voted under the new procedure, indicating a possible unconstitutionality. Other problem related to que lack of adequate criteria to establish the correct nature of the Conventions is the possibility of violation of workers’ human rights. Brazilian Superior Labor Court (TST) refuses appellations based on international treaties, even if they are ILO’s Conventions on human rights. In such scenario, it is as important to present elements to correct characterize ILO’s Conventions as human Rights treaties and to analyze the dimension give to them by Brazilian Constitution, as to study the process of internalization of such treaties, the legislation regarding treaties violations, and the importance of ILO’s Conventions on human rights to Brazilian Superior Labor Court (TST). The first part of the thesis is dedicated to the comprehension of the Human Rights. In the second chapter, we discuss the formation of ILO’s Conventions and their nature as human rights treaties. The third and last chapter, ILO’s Conventions situation in Brazilian Law System is analyzed. The thesis concludes that not all Conventions are human rights treaties; however, Brazilian Constitution is being disrespected in relation to ILO’s Conventions on human rights.